Sporothrix schenckii complex in felines: Analysis of clinical, mycological, environmental and epidemiological factors (Research, Society and Development, 2024)
Sporotrichosis is an infectious and chronic fungal disease caused by fungi belonging to the Sporothrix schenckii complex that affects humans and animals through traumatic implantation of the fungus in the skin. They are dimorphic, saprophytic and geophilic fungi that are widely distributed in nature, especially in soils rich in organic matter. The aim of this study was to understand the clinical, mycological, environmental and epidemiological aspects of the Sporothrix schenckii complex in felines. In order to meet the objectives of this research, a qualitative, descriptive and exploratory data survey was carried out through a bibliographic review based on works published in the last 23 years. Sporothrix spp. is considered to be a complex of at least six cryptic species, in other words, they have similar morphological characteristics but different genotypes. In cats, the incubation period is variable; it usually lasts 14 days. On penetrating the tissue, the micellar form transforms into yeast, which generates an inflammatory response and proliferation of the microorganism at the site, causing papular and nodular lesions which, in some cases, heal spontaneously. Therefore, it is clear that sporotrichosis is caused by dimorphic fungi of the Sporothrix schenkii complex. It is a zoonotic disease of great importance in the context of public health, since it is still a neglected disease and requires robust measures to control. As well as being the most seriously affected, felines are the main transmitters to humans and animals, making them a key point in controlling outbreaks of the disease.